Implementasi model Project-Based Learning (PjBL) untuk meningkatkan kemampuan berpikir kritis siswa pada mata pelajaran IPS di era digital - Syahrani, Andini (Maliki Interdisciplinary Journal, 2026)
The implementation of the Project-Based Learning (PjBL) model is a relevant instructional approach in the digital era to enhance students’ critical thinking skills, particularly in Social Studies (IPS). Technological advancements require students not only to understand social concepts but also to analyze information, identify problems, and generate creative, data-based solutions. This study aims to comprehensively describe the application of PjBL in Social Studies learning and analyze its effectiveness in developing students’ critical thinking skills. The method used is a literature review by examining scientific literature, research reports, and accredited journal articles related to the implementation of PjBL in 21st-century learning contexts. The findings indicate that PjBL encourages active student engagement, improves analytical, collaborative, and reflective skills, and helps students connect Social Studies material with real-world phenomena through the use of digital technologies. Challenges identified include teacher readiness, facility availability, and students’ digital literacy gaps. However, these obstacles can be minimized through teacher training, strengthened school support, and gradual integration of digital media. Overall, PjBL demonstrates strong potential in fostering critical thinking skills in Social Studies students within the digital era.